Combined Effects of Graphite Tailings and Curing Conditions on the Early-Age Performances of Cement Mortar - Hongbo Liu; Yuxin Zhang; Ben Li; Zhongrui Wang (Advances in Civil Engineering)
In this study, the combined effects of different amounts of graphite tailings (GT) as a substitute for sand and three cure methods on the early-age mechanical and material performances of cement mortar have been investigated. The results can be concluded that graphite tailings and hot-water cure method can effectively improve the early strength of cement-based materials and facilitate the formation of high-density calcium silicate hydrate (C-S-H), more Ca(OH)2 (CH), and other hydration products. Simultaneously, the pore structure distribution in the cement mortar is improved to be finer. Finally, this paper explains the mechanism of GT and hot-water curing (HWC) method on early-age performances of the cement mortar through the graphic model and provides the basis for selecting the GT and HWC method on improving early performance requirements for special engineering or rapid repair engineering through the proposed comprehensive quantitative calculation model.